Menuju Integrasi Peng awasan Pupuk Bersubsidi: Sebuah Rancang Bangun Prototipe E-Suplay Chain Management - Sunarto, Hari (Jurnal Manajemen, 2014)
Misappropiation of subsidized fertilizer is one source of disturbance factors that may lead to scarcity of fertilizer supply to farmer and ultimately disturb to national food security program. Along with this, there are many other sources of disturbance in achieving high standard of key performance indicators, namely, 6-precision - precise in fertilizer types, volume, place, time, quality and price. It is a need to minimize disturbances by supervision. By law, fertilizer and pestiside supervisory committees (KP3) at national, provicial and district level asigned to supervice fertilizer acquisition, distribution and usage by farmers. Under the frame of thinking an e-supply chain management and management control system, the KP3 remains head on some issues, among others (a) not refer to Regulation 60/2008 on the System of Internal Control Government, (b) fragmented business processses in reporting, (c) in this digital age still relies on written (paperworks) reports. Triangulation research method is being used in longitudinal study at a time span 2008-2013 to identify the real needs of KP3 then to set up an appropriate prototype of application software. The software integrates the business process among authorities and it works online, During the focus group discussion, KP3 appreciated these efforts. Knowingly finalization process is still long way to go, because it needs to build information technology infrastructure, protocol management and database support, among others, 4.29 million family farmers with attributes. In the early stages, the software can be used to replace paper-based reports with an online electronic statements and a simple diviation analysis.